3D printing as tool for guiding product design: A teaching experience in the ergonomics course - Porsani, Rodolfo Nucci [UNESP]; da Silva, Bruno Borges [UNESP]; Hellmeister, Luiz Antonio Vasques [UNESP]; Medola, Fausto Orsi [UNESP]; Paschoarelli, Luis Carlos [UNESP] (Springer Nature, 2020)
This study reports on the development of a 3D printer and its implementation in Product Design Education as a tool for prototyping and supporting students in the design process. First, it is presented the design and production of the new 3D printer, focused on the user and with differential features that favor the application of concepts of Ergonomic Design. Next, it is described the teaching experience of implementing the 3D printer as a tool for guiding students in prototyping their products to be further tested. The experience demonstrated that students were able to benefit from the possibility of rapid prototyping their concepts of products, as well as to adjust the design of their products taking into consideration the production process of 3D printing.
Keywords: 3D printing; Ergonomics; Product design education; Transdisciplinarity